Serial determination of inferior vena cava dimension and its correlation with clinical cardiopulmonary-cerebral assessment in children with septic shock - Sankaralingam Umaiorubagam; Indumathy Santhanam; Ravichandran Tiraviyam (Wolters Kluwer Medknow Publications, 2022)
Background: Essential step in the management of septic shock is prompt recognition at an early stage and prediction of fluid responsiveness. Existing methods of assessing septic shock in children have limited accuracy. This study was conducted to determine the serial inferior vena cava (IVC) dimension and its correlation with clinical cardiopulmonary-cerebral assessment in children with septic shock. Subjects and Methods: A prospective observational study was conducted from 1 month to 12 years of children with septic shock resuscitated in the emergency department. Serial ultrasound measurements of IVC/aorta ratio were obtained before and after each fluid bolus of 10 ml/kg over 20 min. Chi-square tests were used to find out whether the statistical differences between assessing fluid status with clinical parameters and assessing fluid status with IVC/aorta ratio after fluid boluses were really significant or not. Results: Hundred patients were enrolled and included in the final analysis. Using Chi-square test, there were significant (P < 0.05) strong associations between heart rate, pulse volume, capillary refill time, blood pressure, and IVC/aorta ratio during multiple assessments following fluid boluses. Conclusions: IVC/aorta ratio was statistically significantly associated with volume status and clinical assessment. A single assessment of IVC/aorta ratio did not appear useful. Serial determinations of IVC/aorta ratio emerged statistically significant in the assessment of fluid status in children with septic shock during resuscitation in the emergency department.